Tourists at the League of Nations: conceptions of internationalism around the Palais des Nations, 1925-1946 - Holste, Timo (New global studies, 2016)
This article uses the example of the purpose-built Palais des Nations in Geneva to trace how conceptions of internationalism were used for propaganda purposes by local institutions such as the Association des Intérêts de Genève, (AIG) by the League of Nations’ Information Section and Internal Service, and by private actors surrounding the international organization. The American Committee, whose work was financed by the Carnegie Endowment for International Peace (CEIP), will serve as one example of the latter. Scrutinizing interwar-internationalism through the lens of tourism, this article not only examines the impact of the global features of internationalism on the local level and reveals how the League used the popularity of the Palais des Nations to circumvent the ban on propaganda, it also reassesses the notion of American non-involvement in the League.